The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1148/radiol.2016151407
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Stability of Aortic Aneurysms with Pulse Wave Imaging

Abstract: Purpose:To assess whether the stability of murine aortic aneurysms is associated with the homogeneity of pulse wave propagation within the saccular wall. Materials and Methods:All animal procedures were approved by the institutional Animal Care and Use Committee. Apolipoprotein E and tissue inhibitor of metalloproteinases-1 knockout mice (n = 26) were infused with angiotensin II by using subcutaneously implanted osmotic pumps, with an additional control mouse used for histologic examination (n = 1). Pulse wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The results described here are consistent with previous reports showing an increase in vessel stiffness due to the degradation of elastin and increased collagen turnover [39,32]. This increase in vessel stiffness was also supported by previous reports demonstrating reductions in pulse-wave velocities along the aneurysmal wall [4042]. Previous work using 2D M-mode ultrasound suggested that aneurysm formation typically decreased the Green-Lagrange circumferential strain from around 15% to 3% [32].…”
Section: Discussionsupporting
confidence: 92%
“…The results described here are consistent with previous reports showing an increase in vessel stiffness due to the degradation of elastin and increased collagen turnover [39,32]. This increase in vessel stiffness was also supported by previous reports demonstrating reductions in pulse-wave velocities along the aneurysmal wall [4042]. Previous work using 2D M-mode ultrasound suggested that aneurysm formation typically decreased the Green-Lagrange circumferential strain from around 15% to 3% [32].…”
Section: Discussionsupporting
confidence: 92%
“…Contrast-enhanced ultrasound is very sensitive to detect endoleak after EVAR and can be a good alternative [ 23 ]. Other ultrasound elasticity techniques such as pulse wave imaging or strain analysis were previously reported in preclinical and clinical studies to assess the wall stiffness of abdominal aortic aneurysms [ 24 , 25 ]. Only one study reported its feasibility in the context of EVAR follow-up [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made in a cohort of patients with history of abdominal aortic aneurysm and hypertension, in whom the shape of the waveform was substantially distorted in the most severe cases (Li et al., ). While the clinical impact of the observed 0.09 reduction in the determination coefficient between periodontitis and periodontal health remains speculative, recently published experimental evidence in a murine model demonstrated a less homogeneous propagation in the pulse wave ( R 2 ) in unstable versus stable aortic aneurysms, despite similar PWV values between the groups (Nandlall & Konofagou, ).…”
Section: Discussionmentioning
confidence: 99%